2018
DOI: 10.1007/s12630-018-1050-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of position and positive pressure ventilation on functional residual capacity in morbidly obese patients: a randomized trial

Abstract: clinicaltrials.gov (NCT02121808). Registered 24 April 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This is particularly applicable to morbidly obese patients and term parturients. [121][122][123][124] In addition, gentle FMV between loss of consciousness and beginning laryngoscopy is advocated. • Moderate to high risk of oxygen desaturation: For the patient at higher risk of oxygen desaturation with the onset of apnea, such as those with lower FRC and increased shunt fraction, the optimal pre-oxygenation strategy likely involves use of positive end-expiratory pressure or non-invasive positive pressure ventilation (NIV) during pre-oxygenation, [125][126][127][128] together with back up or reverse Trendelenburg positioning.…”
Section: Pre-oxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly applicable to morbidly obese patients and term parturients. [121][122][123][124] In addition, gentle FMV between loss of consciousness and beginning laryngoscopy is advocated. • Moderate to high risk of oxygen desaturation: For the patient at higher risk of oxygen desaturation with the onset of apnea, such as those with lower FRC and increased shunt fraction, the optimal pre-oxygenation strategy likely involves use of positive end-expiratory pressure or non-invasive positive pressure ventilation (NIV) during pre-oxygenation, [125][126][127][128] together with back up or reverse Trendelenburg positioning.…”
Section: Pre-oxygenationmentioning
confidence: 99%
“…96,98 ''Back up'' or reverse Trendelenburg positioning will help delay oxygen desaturation. [116][117][118][119][120][121][122][123][124] If general anesthesia is elected, careful pre-oxygenation must occur, with a goal of achieving FeO 2 C 0.9. • Apneic oxygenation is recommended during laryngoscopy and intubation of all morbidly obese patients when managed after the induction of general anesthesia.…”
Section: Post-proceduresmentioning
confidence: 99%
“…In this case, severe obesity and intubation difficulties during preoperative airway evaluation were anticipated. Previous studies have shown that head-up [ 7 , 8 ] or beach-chair [ 9 ] positioning improves safe apnea time before the occurrence of significant hypoxemia. Furthermore, NHFC is effective for increasing apnea time under general anesthesia in obese patients and preventing a decrease in peripheral blood oxygen saturation (SpO 2 ) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies have shown a similar positional effect. Couture et al [ 8 ] concluded that in the obese population, positioning patients with their heads above their feet by tilting the table 25 degrees, significantly increases FRC and oxygen storage capacity.…”
Section: Patient Positioningmentioning
confidence: 99%